2012
DOI: 10.1097/cad.0b013e32834f9801
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of the scFv-based fusion protein and its enediyne-energized analogue directed against epidermal growth factor receptor

Abstract: Epidermal growth factor receptor (EGFR), overexpressed in many epithelial tumors, plays important roles in the formation and the development of tumors, and thus it is regarded as a promising target for cancer therapy. Single-chain variable fragment (scFv), an engineered antibody fragment, is generally used for constructing antibody-targeted drugs, owing to its low immunogenicity and high penetration capability into solid tumors. A fusion protein ER(Fv-LDP), consisting of an anti-EGFR scFv and the apoprotein (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…However, the bioactivity of LDP and LDPbased fusion proteins also has gradually garnered our interest in recent years. LDP-based fusion protein can reportedly inhibit the growth of tumours [12]. In the current study, similar results for Fv-LDP were also obtained based on the colony formation assay and the in vivo experiments using mice bearing human hepatoma BEL-7402 and murine transplantable H22 cells ( fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the bioactivity of LDP and LDPbased fusion proteins also has gradually garnered our interest in recent years. LDP-based fusion protein can reportedly inhibit the growth of tumours [12]. In the current study, similar results for Fv-LDP were also obtained based on the colony formation assay and the in vivo experiments using mice bearing human hepatoma BEL-7402 and murine transplantable H22 cells ( fig.…”
Section: Discussionsupporting
confidence: 85%
“…C). The internalization rate of Fv‐LDP was lower than that of other antibody‐based fusion proteins bound to the cell membrane, which suggested that most of the Fv‐LDP might act on the surface of tumour cells but did not directly enter the tumour cells .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, LDP displayed moderate cytotoxicity to human hepatoma Bel-7402 cells with an IC50 value of 7.05 × 10 -5 mol/l and it exerted tumor suppression on hepatoma H22 in Kunming mice [20]. The functional receptor of ES nucleolin was found to be specifically expressed on the surface of angiogenic blood vessels in tumor tissues, which endows ES low toxicity and tumor-specific distribution [7].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of rebuilt molecule remains as potent as that of natural LDM. LDP, which is composed of 110 amino acid residues, showed specific binding capability to various human tumor tissues and displayed moderate cytotoxicity to Bel-7402 cells [20,21]. This specific binding capability and cytotoxicity of LDP implied its potential use as a targeting drug carrier in the design of new anticancer agents.…”
Section: Introductionmentioning
confidence: 99%